Edukasi Kesehatan: Membangun Kesadaran Good Posture untuk Peningkatan Kualitas Kesehatan dan Produktifitas Pelajar SMA Muhmamadiyah 03 Tulangan Sidoarjo - Arti, Widi; Anjasmara, Bagas; Widanti, Herista Novia (Universitas Nusantara PGRI Kediri, 2022)
Good posture is when the head, shoulders, spine, waist, knees and ankles are all in a straight line. Lack of awareness of students about the importance of maintaining good posture will causes bad posture which has the potential to trigger abnormalities in the spine. This community service program is one of the government's efforts to improve the quality of life and productivity with good posture for students at SMA Muhammadiyah 3 Tulangan, Sidoarjo Regency. This program is expected to increase awareness of good posture in students. The method is education with lectures, practice and demonstration methods by using teaching aids as a tool in the educational process. The measuring to measure posture is using the postural zone and for practicing Mckenzie Exercise and Stretch for neck and shoulder pain using a mat and foam roller props. The successful of this program can be seen from the increase in knowledge by 50%, increasing awareness of good posture in students by 75%, increasing the number of questions from students related to the material presented by 50% and the number of students experiencing a significant increase in pre-test and post-test scores by 70%.